Mikroekonomické dopady minimální mzdy na vybrané podniky - Lajtkepová, Eva (Vysoké učení technické v Brně. Fakulta podnikatelská)
I když zákonná minimální mzda není kategorií novou (poprvé byla stanovena již v r.1912 ve státě Massachusetts v USA), v České republice se s ustanovením o minimální mzdě poprvé setkáváme až v novele zákona č. 65/1965 Sb., zákoníku práce, z roku 1990. Konkrétní částka minimální mzdy i podmínky jejího uplatňování potom byly stanoveny usnesením vlády v únoru 1991. Od té doby byla částka minimální mzdy již mnohokrát valorizována (v lednu 2006 byla valorizace minimální mzdy již třináctou změnou). Předkládaná disertační práce se zabývá vybranými dopady minimální mzdy na podniky se zvláštním zřetelem malých a středních podniků (do 250 zaměstnanců). Pozornost je zaměřena jak na poptávkovou stranu trhu práce (akceptace zákonné výše minimální mzdy podniky), tak na stranu nabídkovou (vliv zákonné výše minimální mzdy na ochotu a motivaci nezaměstnaných nabídnout na trhu práce svoji pracovní sílu). Práce je zaměřena na následující stěžejní oblasti : podrobné zmapování vlivu minimální mzdy na podniky a zaměstnanost v ekonomické teorii a v protikladu teorie k výsledkům empirických výzkumů, identifikaci postavení minimální mzdy ve mzdové distribuci v České republice (sekundární výzkum), akceptaci minimální mzdy malými a středními podniky v Jihomoravském kraji (primární výzkum) a ochotu nezaměstnaných pracovat za částku minimální mzdy (primární výzkum). Nedílnou součástí práce je sestavení pomůcky pro potřeby podniku při náboru a přijímání nových pracovníků - rozhodovacích stromů, které poskytují podniku informace o vnějším trhu práce.

Even though the legal minimum wage is not a new thing (it was first set in 1912 in the state of Massachusetts in the USA), we first come across the stipulation of a minimum wage in an amendment to Act No. 65/1965 Coll. of the Labour Code from 1990. The specific level of minimum wage and the conditions for applying it were then set by government resolution in February 1991. Since then the level of minimum wage has been valorised many times (in January 2006 the valorisation of minimum wage was the thirteenth time the minimum wage had been changed). The submitted dissertation deals with selected impacts of the minimum wage on firms, with special consideration to small and medium-sized enterprises (up to 250 employees). Attention is focused both on the demand side of the labour market (acceptance of legal level of minimum wage by firms), as well as on the supply side (effect of the legal level of minimum wage on willingness and motivation of the unemployed to supply their labour on the labour market). The work is focused on the following fundamental areas: detailed mapping of the effect of the minimum wage on firms and employment in economic theory and in contrast to theories for the results of empirical research, identification of the position of minimum wage in wage distribution in the Czech Republic (secondary research), acceptance of minimum wage by small and medium-sized firms in Southern Moravia County (primary research) and willingness of the unemployed to work for the minimum wage (primary research). An integral part of the work is the setting up of aids for the needs of a firm for enrolment and taking on of new employees - decision trees that provide information to the firm on the external labour market.
Keywords: minimální mzda; malé a střední podniky; mzdová distribuce; nábor a přijímání pracovníků; trh práce; zaměstnanost.; minimum wage; small and medium-sized enterprises; wage distribution; enrolment and taking on of new employees; labour market; employment.